2022
DOI: 10.1039/d2en00176d
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular level understanding of advanced carbon dots to enhance maize drought tolerance: modulation of photosynthesis and signaling molecules

Abstract: Drought stress is posing severe threat to the global crop production. Herein, we report a solution to combat drought stress by employing advanced carbon dots, which are rationally designed with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Therefore, we propose that N-CDs could increase crop photosynthesis in drought through light harvesting, photoprotection (PP) (ROS scavenging), and light repairing (upregulated expression of psbA and fast synthesis of the D1 protein). Recent studies demonstrated that CDs and N-CDs could promote the growth of tomatoes, maize, and soybeans under drought stress by modulating rhizospheric properties, nutrient bioavailability, photosynthesis, and phytohormones. However, the mechanism of promoted photosynthesis and whether N-CDs could increase crop yield in drought are still unknown. Thus, the aim of this work is to investigate (1) the mechanism of promoted photosynthesis by N-CDs under drought stress, (2) the advantages of N-CDs in enhancing crop drought tolerance, and (3) the effect of crop yield by foliar-applied N-CDs under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we propose that N-CDs could increase crop photosynthesis in drought through light harvesting, photoprotection (PP) (ROS scavenging), and light repairing (upregulated expression of psbA and fast synthesis of the D1 protein). Recent studies demonstrated that CDs and N-CDs could promote the growth of tomatoes, maize, and soybeans under drought stress by modulating rhizospheric properties, nutrient bioavailability, photosynthesis, and phytohormones. However, the mechanism of promoted photosynthesis and whether N-CDs could increase crop yield in drought are still unknown. Thus, the aim of this work is to investigate (1) the mechanism of promoted photosynthesis by N-CDs under drought stress, (2) the advantages of N-CDs in enhancing crop drought tolerance, and (3) the effect of crop yield by foliar-applied N-CDs under drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…The canola genotype-Rachna and camelina genotype-618 showed a response about plant morpho-physiological parameters under droughtstressed conditions and were identi ed as drought-tolerant genotypes as compared to the sensitive genotypes; canola genotype-Super and camelina genotype-611 which showed a drastic reduction in plant growth. Hu et al [111] revealed that Si responses had a favorable impact on development in tolerant genotypes under both control and stressful settings, suggesting that they could be yet another signi cant component. The applications of Si upregulate stomatal functions which permit some carbon xation by drought-tolerant cultivars as compared to sensitive genotypes may lead to increased water use effectiveness [112,113].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that carbon dots may render soybeans to tolerate drought better. The association of carbon dots with aquaporins was also studied intensively in maize by Wang et al, and their findings demonstrated that foliar application of carbon dots increased the amount of water taken in by maize roots (89.3%) through the buildup of Pro (36.3%) and ABA (6.9%), as well as increased activity of the major aquaporins linked to water uptake (2.3–7.6% increase in related gene expression) …”
Section: Nanoenabled Strategies For Plant Stress Tolerance In Respons...mentioning
confidence: 98%
“…Photosynthesis is restricted when plants are stressed. , Nanomaterials can maintain plant photosynthesis at normal levels and promote root water uptake (Figure ). The NMs can increase the expression of ctg121 and ZemaCp002 , thus maintaining the stability of PSII . Under drought stress, NMs can boost photo reaction activity and release more energy.…”
Section: Molecular Mechanisms Of Nanoenabled Strategies Enhanced Stre...mentioning
confidence: 99%
See 1 more Smart Citation